Current advances in development of new docetaxel formulations. (4th March 2019) - Zhang, Enhui; Xing, Ronge; Liu, Song; Li, Pengcheng
ABSTRACT: Introduction : Docetaxel (DTX) is one of the most important chemotherapeutic agents and has been widely used for treatment of various types of cancers. However, the clinical chemotherapy of DTX gives many undesirable side effects due to the usage of organic solvent in the injection and its low selectivity for tumor cells. With the evolution of pharmaceutical technologies, great efforts have been paid to develop new DTX formulations to overcome these problems. Areas covered : This review provided an overview of the preparation and activities of new DTX formulations, which were classified by administration methods, including injection, oral, transdermal and rectal administration. Besides, up to date information of the clinical status of new DTX formulations was summarized. We also discussed the challenges and perspectives of the future development of DTX formulations. Expert opinion : There have been numerous studies on new DTX-based formulations in recent years, and many of them exhibited significantly enhanced anti-tumor and targeting activity compared with DTX in preclinical studies. However, only a few entered clinical trials, and none has been approved into market. The clinical translation of experimental drug faces many hurdles, including the limited knowledge of nanomedicine and oncology, safety issues, controllable and reproducible production.